Analisis Kinerja Sistem Manajemen Agribisnis Cabai Merah Di Kabupaten Deli Serdang Sumatera Utara: Performance Analysis of the Red Chili Agribusiness Management System in Deli Serdang Regency, North Sumatra - Sherly, Ayu; Safrida, Delima; Asmawati, Asmawati (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study analyzes the performance of the red chili agribusiness management system in Deli Serdang Regency. Based on data from 40 farmers and using a 0-200 assessment scale, the results indicate that overall performance is in the "Fairly Good" category with a score of 132.03. While organizational and actualization aspects have been implemented, several critical activities remain suboptimal. The main weaknesses lie in the absence of written planning, low use of certified seeds, and inadequate marketing promotion. To improve performance to the "Good" category, the study recommends that farmers develop written and comprehensive farming plans, consistently use certified superior seeds, and develop broader marketing strategies.